Epidemiology and Outcome of Convulsive Status Epilepticus - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
The results of the North London Convulsive Status Epilepticus in Childhood Surveillance Study (NLCSESS) are used to develop a new treatment protocol, by researchers at the Institute of Child Health, and Great Ormond Street Hospital for Children, London, UK.